Prediction of cardiovascular events by central blood pressure using radial tonometry in type 2 diabetes mellitus patients - Min-Sik Kim; Seon-Ah Cha; Gee-Hee Kim (Clinical Hypertension, 2022)
Abstract Background High blood pressure (BP) and type 2 diabetes mellitus (T2DM) are major causes of atherosclerotic cardiovascular disease (ASCVD) and heart failure (HF). Central blood pressure (CBP) is more predictive of ASCVD than is brachial BP; however, an association of CBP with ASCVD has not been found in T2DM patients. We evaluated the impact of CBP and the association between optimal level of noninvasively measured CBP and office BP in T2DM patients based on composite outcome of ASCVD, HF, and complications of hypertension. Methods Patients were enrolled from June 2011 to December 2015 and were followed up through December 2019. CBP was measured using radial tonometry. The primary endpoints were composite outcome of ASCVD, HF, and hypertension-induced complications such as left ventricular hypertrophy, retinopathy, and proteinuria. Results During the 6.5-year follow-up period, 515 patients were enrolled in the study. A total of 92 patients (17.9%) developed primary endpoints. The mean age of subjects was 61.3 ± 12.1 years and 55% (n = 283) were male. Patients who developed primary endpoints were older (65.3 ± 9.5 years vs. 60.5 ± 12.4 years) and had lower high-density lipoprotein (36.6 ± 9.4 mg/dL vs. 41.8 ± 11.1 mg/dL), higher CBP (123.6 ± 20.6 mmHg vs. 118.0 ± 20.6 mmHg), and higher pulse pressure (61.3 ± 16.6 mmHg vs. 56.5 ± 15.1 mmHg) than subjects without primary endpoint development. After adjustment for various risk factors, CBP was an independent predictor for primary endpoints (hazard ratio, 1.14; 95% confidence interval, 1.02–1.27; P = 0.016). In addition, the association of CBP and primary endpoints showed a U-shaped curve with the lowest incidence at CBP 118 mmHg and systolic BP about 128 mmHg. Conclusions We show the importance of CBP measurements in T2DM patients and present a cutoff value for ASCVD events and hypertension-induced complications.